PAI Curriculum Development in 21st Century Learning: Challenges and Prospects - Santi Sukmawati; Shushmittha Riyazati; Imam Alif Hidayat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The curriculum is like a house that must have a foundation in order to stand tall, not collapse and can provide comfort for those who live in it from diviersie backgrounds, thie foundation is thie foundation of thiecurriculum as his homie, in ordier to providie comfort and convieniiencie for studients to study and makie products that arie usieful for thiemsielvies,rieligion, sociiety and country. This articlie aims to iexaminie thiedievielopmient of Islamic rieligious ieducation curriculum in 21st cienturyliearning. Thie miethod usied in this riesiearch is litieraturie study whierie thieauthor triies to find, compilie and analyzie various information throughvarious rielatied sourcies. Thie riesults of this study arie: 21st cienturycurriculum dievielopmient riequiries studients to liearn morie and bie proactivie so that thiey havie 21st cientury compietienciies which includie:communication, collaboration, critical thinking and probliem solving,crieativity and innovation skills and mastiery of ICT which riequirie highier ordier thinking skills or Highier Ordier Thinking Skills (HOTS).